The Emerging Paradigm Shift in Social Work - in the Context of the Current Reforms of European Social Work Education - Sigrún Júlíusdóttir (Social Work & Society, 2006)
The century-old profession of social work has been characterized, among other things, by ideological commitment and political alertness. However, it has also been accompanied by diverging positions and professional invisibility. This has been perceived as both a strength and a weakness for social workers among other traditional helping professions — of which most are now academic or striving for that. It is argued here that social work is about to change its position, developing from the status of a semi-profession towards maturity and full professionalization. For contemporary social work, the challenge is thus to reconstruct old experiences and narratives as professional integrity, visibility and power in a qualitative work-through process. The clarification and rethinking of themes such as invisible loyalties, dichotomous thinking, conflictual positions, and incompatible meaning of social work research are highlighted as crucial tasks on the path to professional maturity. The increasing interest in and acknowledgement of theory and research in education and professional practice is, alongside an increased, although still ambivalent, emphasis on evidence – knowledge – or information-based practice, a sign of an epistemological change. New ways of thinking, whereby theory, practice, and research are viewed as an integrated, continuous interplay, may be defined as a paradigm-shift. This emerging paradigm shift and epistemological change in social work simultaneously implicates an identity transformation, a role shift. Both first- and second-order change are necessary for facilitating developmental changes. First-order change can be achieved by structural reforms or technical interventions. On the other hand, processes of dynamically reconstructed outcomes imply second-order change, meaning that things become qualitatively different from before. The current reform taking place through the Bologna process is an example of this. A case illustration from the University of Iceland is presented where the pros and cons ...